PENGARUH WORK-LIFE BALANCE, PENGEMBANGAN KARIR, DAN KOMPENSASI TERHADAP TURNOVER INTENTION PADA GENERASI Z DI E-COMMERCE - Irawati, Sherly; Meilani, Yohana F. C. P. (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The aims this study is to analyze the effect of work-life balance, career development, and compensation on turnover intention in Generation Z in e-commerce marketplace companies in Jabodetabek. This study uses a quantitative method, where primary data is collected through online questionnaires from 161 generation Z employees in Jabodetabek e-commerce companies. The data were analyzed using smartPLS 4.1.0.2 to test the research hypotheses. Based on the analysis, it was found that work-life balance and career development have a negative and significant effect on turnover intention of Generation Z employees in Jabodetabek e-commerce companies. Meanwhile, compensation has a negative but insignificant effect on the turnover intention of Generation Z employees in the same company. However, this research model does not explain well and has weak predictive ability on turnover intention (R²=0.131, Q²=0.073), so it needs to be tested further with a larger population and additional independent variables. This study can help the management of e-commerce marketplace companies to continue to evaluate compensation, improve career development programs, and offer work flexibility to increase the loyalty of generation Z employees.